Podem pequenas variações na altitude e na ordem de riachos influenciar a estrutura das comunidades de moluscos? - Sá, Roger Lopes de (2012)
The influence of small gradients of altitude (0-500 meters) and order (1st to 4th) in the spatial distribution of mollusk communities was studied, based on 40 samples collected in a watershed of a temperate climate region, in Brazil. Richness was higher in lower ranges of altitude (0-100), and increased with the increase of orders, independently of altitude. However, composition and proportional abundance of species of the communities were not structured by the environmental gradients. The small influence of landscape factors on the spatiality of many abiotic factors, and the tolerance of many species to variations in the environmental factors analyzed determined these results. The proximity of the lower of altitudes with a transitional relief area, and the large width of the 4th order streams, which favored a higher number of ecological niches, provided higher complexity to the sites localized in these areas, allowing the occurrence of higher richness. The existence of patchy spatial structured pattern in good environmental conditions determined the absence of the proportional abundance of species. However, few landscape heterogeneity and possibly, interference of vertebrate vectors in the dispersion of the freshwater mollusks hinder to find clear patterns of spatial distribution.